Combined congenital melanocytic nevus arising on mongolian spot. - Torsello, P.; D’Ambrosio, E. (European Journal of Pediatric Dermatology, 2014)
The combined nevus, often present from the earliest stages of life (1, 2) contains two populations, exceptionally three, of cytologically different melanocytes, usually a common melanocytic nevus formed by rounded cells and a nevus with dendritic melanocytes – blue nevus –. Clinically our nevus was characterized by onset in the site of Mongolian spot. Histologically the deep component was that of a blue nevus with predominantly perifollicular distribution (Fig. 2); the surface component seemed a common dermal melanocytic nevus because it showed a grenz zone below the epidermis, lower melanocytes pigmented, that even lower were less pigmented and less compact for the presence of fibrosis. The two nevi were both made from fusiform melanocytes so it was difficult to establish the boundaries.